Effect of Cigarette Smoking on Peak Expiratory Flow Rate (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Cigarette smoking is an intractable public health problem that carries a threat to the health of the entire population. Smoking is a known risk factor for chronic obstructive pulmonary diseases, cardiovascular diseases, certain cancers especially lung cancer.Objectives:To assess the effect of cigarette smoking on peak expiratory flow rate (PEFR) among cigarette smokers and examine whether PEFR differs between cigarette smokers and non-smokers.Materials and Methods: This is cross-sectional comparative study was done for one year from July 2014 to June 2015. A total of 150 subjects were recruited from the medicine and allied outpatient departments of Mymensingh Medical College Hospital and Mymensingh locality. They are divided into 50 non-smokers (Group I) and 100 smokers (group II) with a duration of smoking 5-10 years (group IIA) and more than 10 years (Group IIB). PEFR was recorded by using Wright’s mini Peak flow meter. A questionnaire including demographic data was completed in all cases. The data were collected and analyzed using SPSS version 11.5.Results: Mean PEFR among non-smokers was 449.20±6.83 L/min whereas among smokers of 5-10 years duration(Group IIA) and above 10 years duration (Group IIB),  it was 301.20±2.17 L/min and 297.80±2.54 L/min respectively. Mean PEFR values were significantly lower in smokers than non-smokers of both groups.Conclusion: Cigarette smoking has deleterious effects on lung function causing a significant reduction of PEFR in smokers compared to nonsmokers. Coordinated national strategies for tobacco prevention, cessation, and control are essential for the establishment of a smoke-free environment.JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 165-167